A novel CDKN2A variant (p16L117P) in a patient with familial and multiple primary melanomas. (3rd May 2019) - Li, Christopher; Liu, Tong; Liu, Bin; Hernandez, Rolando; Facelli, Julio C.; Grossman, Douglas
Abstract: Germline mutations in CDKN2A (p16) are commonly found in patients with family history of melanoma or personal history of multiple primary melanomas. The p16 tumor suppressor gene regulates cell cycle progression and senescence through binding of cyclin‐dependent kinases (CDK) and also regulates cellular oxidative stress independently of cell cycle control. We identified a germline missense (c.350T>C, p.Leu117Pro) CDKN2A mutation in a patient who had history of four primary melanomas, numerous nevi, and self‐reported family history of melanoma. This particular CDKN2A mutation has not been previously reported in prior large studies of melanoma kindreds or patients with multiple primary melanomas. Compared with wild‐type p16, the p16 L117P mutant largely retained binding capacity for CDK4 and CDK6 but exhibited impaired capacity for repressing cell cycle progression and inducing senescence, while retaining its ability to reduce mitochondrial reactive oxygen species. Structural modeling predicted that the Leu117Pro mutation disrupts a putative adenosine monophosphate (AMP) binding pocket involving residue 117 in the fourth ankyrin domain. Identification of this new likely pathogenic variant extends our understanding of CDKN2A in melanoma susceptibility and implicates AMP as a potential regulator of p16.